Determinants of Poverty in Indonesia: Does Per Capita Income Matter? - Imantria, Benny (Universitas Negeri Semarang, 2024)
Poverty in Indonesia has decreased significantly over the past 50 years, but per capita income does not yet indicate deprivation of basic needs. This study aims to identify the determinants of poverty in Indonesia through an economic and social aspect. Data sample used includes poverty rates and socio-economic aspects from 34 provinces in Indonesia for the period 2015-2022, which were analyzed using panel data regression with random effect model. The novelty of this study lies in the socio-economic variables representing financial capability and basic needs. This study found that per capita income, average years of schooling, life expectancy, access to clean water, and access to electricity have negative and significant effects, while unemployment, Gini coefficient, and poverty line have positive and significant effects on poverty in Indonesia. Poverty alleviation can be accelerated not only by increasing per capita income, but also by government policies that equalize income distribution and reduce deprivation of basic needs. Policymakers are expected to improve economic growth, education, healthcare, access to clean water and electricity, reduce income inequality and unemployment, and maintain purchasing power to alleviate poverty in Indonesia.